Reversing the Tide: Priorities for HIV/AIDS Prevention in Central Asia - Godinho, Joana; Renton, Adrian; Vinogradov, Viatcheslav; Novotny, Thomas; Rivers, Mary-Jane; Gotsadze, George; Bravo, Mario (Washington, DC: World Bank, 2012)
Although the number of reported cases of HIV in Central Asia is still very low, the growth rate of the epidemic (about 500 cases in 2000 to over 12,000 in 2004) is a cause for serious concern. Central Asia lies along the drug routes from Afghanistan to Russia and Western Europe, and it is estimated that it has half a million drug users, of which more than half inject drugs. Without concerted action, we may expect to see the rapid development of an HIV epidemic concentrated among injecting drug users over the next four or five years, followed by the spread among the 15- to 30-year-old population, with sexual transmission as the predominant mode. This would follow the pattern of the epidemic in other regional countries such as Russia, Ukraine, and Moldova.